In praise of folly: international administration and the corruption of humanity - BAIN, WILLIAM (International affairs (London), 2006)
Advocates of international administration tend to embrace conduct and utterance that proposes to vindicate fundamental human rights and freedoms by suspending an important part of its content: the principle that human beings should not be subject to coercion except where they have given their consent. This article begins by arguing that the character of this dilemma is obscured by a vocabulary of technique that divests the category 'international administration' of its normative coherence. In fact, international administration discloses two distinct modes of association-contract and trust-which presuppose different values, different obligations, and different expectations. The article proceeds in arguing that a trust instituted among equals is susceptible to objection in so far as trustee and beneficiary are necessarily joined in a coercive relationship that rules out the possibility of consent. The article concludes by arguing that recent attempts at reconciling this sort of relation with the demands of human rights entails a kind of corruption that is intelligible in making ordinary language correspond with the ideal, so that what was once described as the denial of human dignity-subjection to alien rule-is now described as the promotion and protection of fundamental human rights.